2023
DOI: 10.3390/s23136089
|View full text |Cite
|
Sign up to set email alerts
|

A Procedure for Taking a Remotely Controlled Elevator with an Autonomous Mobile Robot Based on 2D LIDAR

Abstract: Navigating between the different floors of a multistory building is a task that requires walking up or down stairs or taking an elevator or lift. This work proposes a procedure to take a remotely controlled elevator with an autonomous mobile robot based on 2D LIDAR. The application of the procedure requires ICP matching for mobile robot self-localization, a building with remotely controlled elevators, and a 2D map of the floors of the building detailing the position of the elevators. The results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The analysis of the paths obtained suggested the definition of a navigation tree to reduce the complexity of the stationary delivery problem and avoid the use of genetic algorithms. Complementarily, in a previous work [31], we demonstrated that a mobile robot using 2D LiDAR and ICP matching for self-localization could take a remotely controlled elevator and navigate between floors, so this proposal is used for floor navigation.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The analysis of the paths obtained suggested the definition of a navigation tree to reduce the complexity of the stationary delivery problem and avoid the use of genetic algorithms. Complementarily, in a previous work [31], we demonstrated that a mobile robot using 2D LiDAR and ICP matching for self-localization could take a remotely controlled elevator and navigate between floors, so this proposal is used for floor navigation.…”
mentioning
confidence: 82%
“…The spatial information involves the position of all possible destinations as well as the navigable areas available to reach these destinations [24,25] and allows the use of a graph search algorithm to obtain an optimal path [26]. The operational information involves the procedures to navigate in the building such as interacting with elevators [27][28][29][30][31] and doors [32][33][34][35][36]. The spatial information is usually referenced in a 2D map [37,38] which describes the metric, topology, navigable areas, and appearance of the application scenario [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from a known waypoint (or node position) on the map, the A* algorithm determines which sequence of nodes in the navigation tree are to be visited to complete an exploratory mission. This sequence includes the possibility of accessing elevators to navigate between the floors of the building during a mission [64]. Figure 4 depicts an example of the planned path from the current robot position (violet ring) to a destination defined by a key waypoint (black ring).…”
Section: Methods For Path-planningmentioning
confidence: 99%
“…There are no large robots available for laser welding within vast LNG cargo holds that are capable of movement between different levels. Although studies such as [10][11][12] have been conducted on robots with elevator-like movements for logistics and transportation purposes, laser welding robots face the challenge of accommodating very thick cables due to issues such as wiring, cooling, and power requirements. Technical and procedural solutions are required to address these issues.…”
Section: How To Secure the Precision Of Mobile Robotsmentioning
confidence: 99%